Exposure‐response modeling for extrapolation from adult to pediatric patients who differ with respect to prognostic factors: Application to everolimus - Thomas Dumortier; Günter Heimann; Martin Fink (Wiley, 2021)
Abstract Pediatric extrapolation is essential for bringing treatments to the pediatric population, especially for indications where the recruitment of pediatric patients into clinical trials is difficult and where fully powered trials are impossible. Often a similar exposure‐response relationship between adult and pediatric patients can be assumed, but just matching exposures can be misleading when some prognostic factors for efficacy differ between those two patient populations. We present an example in liver transplantation where different study designs led to different (time‐dependent) hazards between populations. Only after accounting for this difference an apparent mismatch between the extrapolation from adults and the pediatric study could be resolved. This article also exemplifies a clear scientific, methodological approach of pediatric extrapolation, including model building in adults, extrapolation to pediatrics, qualification of the extrapolation, and derivation of the actual pediatric efficacy.